Enhanced chroma feature extraction from HE-AAC encoder - Fink, Marco; Biswas, Arijit; Kellermann, Walter (Audio Engineering Society Convention, 2012)
A perceptually enhanced chroma feature extraction during the HE-AAC audio encoding process is proposed. Extraction of chroma features from the MDCT-domain spectra of the encoder and its further enhancement utilizing the perceptual model of the encoder is investigated. The main advantage of such a scheme is a reduced computational complexity when both chroma feature extraction and encoding is desired. Specifically, the system is designed to produce reliable chroma features irrespective of the block switching decision of the encoder. Three methods are discussed to circumvent the poor frequency resolution during short blocks. All proposed enhancements are evaluated systematically within a well-known state-of-the-art chord recognition framewor